THE GREEN MSME DRYING TECHNOLOGY MODEL AND ITS IMPACT ON THE ADDED VALUE OF COFFEE FARMERS IN ACEH - Dedy Darmansyah; Hartini; Qhisthina Atikah; Ina Yuyun (RADJA PUBLIKA, 2025)
Drying is a critical post-harvest stage for coffee, as it directly determines the final quality, economic value, and ultimately, farmers' income. Most farmers in Aceh Tengah and Bener Meriah still rely on conventional methods, such as drying coffee directly on tarps or non-standard racks. These practices often result in high moisture content, significant physical defects, and consequently, lower selling prices. This study analyzes the effectiveness of a